2004
DOI: 10.1093/geront/44.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Quality, Cost, Staffing, and Staff Mix

Abstract: For nursing homes to achieve good resident outcomes, they must have leadership that is willing to embrace quality improvement and group process and see that the basics of care delivery are done for residents. Good quality care may not cost more than poor quality care; there is some evidence that good quality care may cost less. Small facilities of 60 beds were more likely to have good resident outcomes. Strategies have to be considered so larger facilities can be organized into smaller clusters of units that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(134 citation statements)
references
References 39 publications
4
126
3
1
Order By: Relevance
“…We found that no organizational factor was significantly associated with the ADL of older adults. This is inconsistent with previous research, which has shown that for-profit ownership and higher staffing levels, in particular, more licensed nursing hours at nursing homes, affect the ADL of older adults (Rantz et al, 2004). Lee (2009) reported that ownership, number of beds, and staff turnover rate of organizations were related to deterioration in quality of service, including decline in ADL, in Korean LTCHs.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We found that no organizational factor was significantly associated with the ADL of older adults. This is inconsistent with previous research, which has shown that for-profit ownership and higher staffing levels, in particular, more licensed nursing hours at nursing homes, affect the ADL of older adults (Rantz et al, 2004). Lee (2009) reported that ownership, number of beds, and staff turnover rate of organizations were related to deterioration in quality of service, including decline in ADL, in Korean LTCHs.…”
Section: Discussioncontrasting
confidence: 64%
“…Predictors to affect ADL were age (Peres, Verret, Alioum, & BarbergerGateau, 2005), gender (Peres et al), baseline ADL (Wu et al, 2000), incontinence (Wu et al), pressure ulcers (Buttar, Blaum, & Fries, 2001 (Barberger-Gateau, Fabrigoule, Amieva, Helmer, & Dartigues, 2002). Organizational factors that were reported to affect patient dependence in ADL in nursing homes were ownership (Harrington, Woolhandler, Mullan, Carrillo, & Himmelstein, 2001), number of beds (Rantz et al, 2004), licensed nursing hours (Horn, Buerhaus, Bergstrom, & Smout, 2005), staffing levels (Bostick, Rantz, Flesner, & Riggs, 2006), and registered nurse (RN) turnover (Collier & Harrington, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The QI rank (or percentile), therefore, provides a relative measure of overall quality within a group of nursing homes. Instead of employing the QI rank method utilized by [20], [23] and [24] classify nursing homes based on their individual QI scores and compare these scores to established QI thresholds [27]. The conglomeration of the individual QI ratings yielded an overall classification for the facility-good, average, or poor.…”
Section: Nursing Home Care Quality Modelsmentioning
confidence: 99%
“…A study conducted by Marilyn et al (2004) indicates that presence of Nurse Mentors as teachers in clinical setup was highly appreciated by the students. His study showed that above all, a job that was regarded as permanent and perceived as a connection to Nursing education by the Nurse Mentors, caused them to be more receptive towards students learning process and significantly boosted the job satisfaction score, with a marginal increment for not having to work unpaid overtime (Gray and Smith, 2000).…”
Section: Introductionmentioning
confidence: 99%